Performance Evaluation of Unsignalized Intersections with Unofficial Traffic Control Officers (Case Study of Bong Cino Intersection City of Madiun) - Achmad Luthfi Prastyo; Nurul Hidayati; Senja Rum Harnaeni (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Simpang Bong Cino is an uncited interchange that in the field is arranged by unofficial officers to be located in the outer cordon that connects Madiun and Magetan Regencies with Madiun City. This study aims to assess the performance of intersections with officers, without officers, and using Traffic Signal Control Tools, as well as recommend the best type of arrangement. The primary data collection used is an interchange inventory survey and a classified deflection movement survey which is carried out twice on the same day and time on different dates, namely Wednesday, June 15 and 22, 2022, which is then analyzed using MKJI 1997. The results of the analysis obtained The existing condition of the intersection with traffic control officers, obtained a degree of saturation of 0.75, a major road delay (DMA) of 6.46 sec / smp, a minor road delay of 14.96 sec / smp and an intersection delay of 12.88 sec / smp. If without a traffic control officer, a saturation degree value of 0.74 is obtained, the major road delay is 6.31 sec/smp, the minor road delay is 15.43 sec/smp and the interchange delay is 12.66 sec/smp. When set up with the Traffic Signal Control Tool, a saturation degree of 0.51 was obtained and the average delay for the entire intersection was 20.14 sec/smp. The best interchange setting recommendation is intersection without unofficial officers.